Implementation of Electronic Patient-Reported Outcomes for Symptom Monitoring in a Large Multisite Community Oncology Practice: Dancing the Texas Two-Step Through a Pandemic. (2021) - Patt, Debra; Wilfong, Lalan; Hudson, Kathryn Elizabeth; Patel, Amila; Books, Holly; Pearson, Ben; Boren, Rhonda; Patil, Shrutika; Olson-Celli, Kristin; Basch, Ethan
Abstract : PURPOSE: Among patients receiving chemotherapy, symptom monitoring with electronic patient-reported outcomes (ePROs) is associated with improved clinical outcomes, satisfaction, and compliance with therapy. Standard approaches for ePRO implementation are not established, warranting evaluation in community cancer practices. We present implementation findings of ePRO symptom monitoring across a large multisite community oncology practice network. METHODS: Patients initiating a new systemic therapy at one of the 210 practice sites at Texas Oncology were invited to use the Navigating Cancer ePRO platform, with stepped-wedge implementation from July to December 2020. Participating patients received a weekly prompt by text message or e-mail to self-report common symptoms and well-being. Severe self-reported symptoms triggered a real-time notification to nursing triage to address the symptom. Enrollment and compliance were systematically tracked weekly with evaluation of barriers and facilitators to adoption and sustainability. RESULTS: Four thousand three hundred seventy-five patients planning systemic treatment were enrolled and participated. Seventy-three percent (1, 841 of 2, 522) of enrolled patients completed at least one ePRO assessment. Among these individuals, 64% (16, 299 of 25, 061) of available weekly ePRO assessments were completed. Over a 10-week period, compliance declined from 72% to 52%. Barriers currently being addressed include lack of a second reminder text or e-mail prompt, inconsistent discussion of reported ePROs by clinicians at visits, and COVID-related changes in workflow. Facilitators included ease of use and patient and staff engagement on the importance of PROs for symptom management. CONCLUSION: ePROs can be effectively implemented in community oncology practice. Utilization of ePROs is high but diminishes over time without attention to barriers. Ongoing work to address barriers and optimize compliance are underway.